1997
DOI: 10.1111/j.1745-4565.1997.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POTENTIAL FOR CRYPTOSPORIDIUM PARVUM OOCYST SURVIVAL IN BEVERAGES ASSOCIATED WITH CONTAMINATED TAP WATER

Abstract: Cryptosporidium parvum is an enteric coccidian protozoan which produces an environmentally stable oocyst that is excreted in the feces of infected individuals. There have been ten documented water borne outbreaks in North America. If food or beverages were prepared from contaminated water, that food or beverage would also be a hazard. The objective of this study was to evaluate the survival of Cryptosporidium parvum in beverages. Viability of oocysts, as determined by morphology decreased over 24 h exposure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 11 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The survival of Cryptosporidium in fruit juice has been investigated using vital dyes. One study reported the survival of a significant proportion of oocysts inoculated into orange juice (pH 3.9) stored at 4°C and at 22°C for 24 h (Friedman et al, 1997). When naturally present, oocysts recovered from stored concentrates obtained in Egypt, were tested using vital dyes and 4-or 5-week-old Swiss albino mouse infectivity.…”
Section: Occurrence and Survival Of Cryptosporidium Spp In Fruit Juicementioning
confidence: 99%
“…The survival of Cryptosporidium in fruit juice has been investigated using vital dyes. One study reported the survival of a significant proportion of oocysts inoculated into orange juice (pH 3.9) stored at 4°C and at 22°C for 24 h (Friedman et al, 1997). When naturally present, oocysts recovered from stored concentrates obtained in Egypt, were tested using vital dyes and 4-or 5-week-old Swiss albino mouse infectivity.…”
Section: Occurrence and Survival Of Cryptosporidium Spp In Fruit Juicementioning
confidence: 99%
“…Friedman et al. (1997) describe large reductions in the percentage of oocysts with four sporozoites visible in various beverages including beer, cola, orange juice and infant formula over a 24‐h period.…”
Section: Discussionmentioning
confidence: 99%
“…This may be relevant to certain food types such as icings, syrups and dry goods. There is also a report on reduction in viability in acidified and carbonated beverages (Friedman et al. 1997).…”
Section: Introductionmentioning
confidence: 99%
“…C. parvum has been found in cider, unpasteurized milk and in the faeces of cattle and other livestock Cliver, 1999, 2001;Dixon, 2009). Water infected with sewage is often thought to be the source of contamination involving fresh fruits and vegetables and beverages (Friedman et al, 1997). The oocysts of C. parvum can survive in fresh, brackish and saltwater for a number of months (Gomez-Couso et al, 2003) and have been isolated from clams, oysters and other shellfi sh (Fayer et al, 1998).…”
Section: Cryptosporidiosismentioning
confidence: 99%